SEVERITY SCORING PADA PASIEN KRITIS - Yulianto, Susilo; Indriasari (E-Journal Widya Kesehatan dan Lingkungan, 2020)
The scoring system used in the management of critical patients has been introduced and developed since more than 30 years. The system allows assessment of disease severity and provides a prediction of mortality in the hospital. The scoring system consists of outcome prediction scores (APACHE, SAPS, MPM) and organ dysfunction scores (SOFA, MODS). In addition, the scoring system is also divided based on data collection methods, namely: anatomical score, therapeutic weighted score, specific organs, physiological assessment, simple scale (simple), and specific diseases. APACHE, SAPS, MPM, SOFA and MODS are scores that are often used in the ICU, these scores have a certain specificity and level of discrimination, where these scores are still being developed taking into account local conditions and the use of drugs to support the cardiovascular taking into account local conditions and the use of drugs to support the cardiovascular system, . In conclusion, the Severity of Illness score is a tool designed to predict and evaluate, from various perspectives, to predict patient outcomes.Most scoring systems are the result of multivariate regression analysis applied to large databases to identify the most relevant factors in predicting mortality.